Pengaruh Komunikasi Kepemimpinan dan Motivasi Kerja terhadap Kinerja Guru SMP - Wardiman Wardian (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2010)
Communication skill of leadership is influence followers and involves the use of power by the leader and follower acceptance. Permissibility affect follower connect hooks to satisfy follower satisfaction. Now the leaders should not be branded again as a leader who is good or not good, but we can only say a leader is impressive in one-one situations, but not memorable in other situations. Impressiveness leadership communication may also reserved dipertingkatkan in the same way there is with modifying factors in order to become more stable situation.